Perencanaan Rehabilitasi Drainase Ruas Jalan Telaga Warna Tlogomas Malang - Azwar, Erizaldy; Pandulu, Galih Damar; Primasworo, Rifky Aldila; Sadillah, M.; Rahma, Pamela Dinar (Universitas Tribhuwana Tunggadewi Malang, 2022)
The people of the Tlogomas sub-district, especially the residents of RT 07 RW 06, are facing the problem of rainwater inundation on the Telaga Warna road. Therefore the Tlogomas sub-district community needs competent personnel with Civil Engineering expertise and requires supporting equipment in terms of surveys and analysis equipment to plan drainage rehabilitation. This community service activity uses the AutoCAD program to apply topography measurement technology applications and drainage designs. The results of the topographic survey describe the longitudinal and transverse sections of the Telaga Warna road section. The cross-sectional design of the drainage channel using precast concrete/U-Gatter measuring 100x100 cm. From the calculation of the volume of drainage and rehabilitation needs for the Telaga Warna road section, a cost of Rp. 676,187,000,-. As a result of this community service activity, partners receive assistance in terms of planning so that a good and efficient implementation of the drainage rehabilitation plan is obtained.ABSTRAKMasyarakat kelurahan Tlogomas khususnya warga RT 07 RW 06 menghadapi permasalahan genangan air hujan di ruas jalan Telaga Warna. Oleh karena itu masyarakat kelurahan Tlogomas membutuhkan kompetensi personil yang mempunyai keahlian Teknik Sipil serta membutuhkan peralatan yang mendukung dalam hal survei maupun peralatan analisa untuk merencanakan rehabilitasi drainase. Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah penerapan aplikasi teknologi pengukuran topografi serta desain drainase menggunakan program AutoCAD. Hasil survey topografi menggambarkan penampang memanjang dan melintang ruas jalan Telaga Warna. Serta desain penampang saluran drainase yang menggunakan beton precast/ U-Gatter ukuran 100x100 cm dari hasil perhitungan volume kebutuhan rehabilitasi drainase ruas jalan Telaga Warna dibutuhkan biaya sebesar Rp. 676.187.000,-. Hasil dari kegiatan pengabdian masyarakat ini, mitra memperoleh pendampingan dalam hal perencanaan sehingga diperoleh implementasi perencanaan rehabilitasi drainase yang baik dan efisien